Economic Analysis of Oyster Farming (Crassostrea sp.) in Sakoshi Bay, Japan: A Case Study of Tomita Suisan Co., Ltd. - Fadil Zainal Mustofa; Ine Maulina; Asep Agus Handaka (Universitas Muhammadiyah Malang, 2025)
Oysters (Crassostrea sp.) represent a high-value aquaculture commodity in Japan, contributing significantly to the coastal economy. This study investigates the economic viability of oyster farming in Sakoshi Bay, Ako City, Hyogo Prefecture, using Tomita Suisan Co., Ltd. as a case example. Employing a descriptive method and a quantitative approach, including direct field observations, the research focuses on farming practices in calm, coastal waters using the floating raft technique. Two oyster varieties—Igashi and Furimi—are cultivated. Economic analysis was conducted based on investment and operational costs, along with key financial indicators: Revenue-Cost Ratio (R/C) and Payback Period (PP). The analysis yielded an R/C ratio of 4.32 and a PP of 11 months, indicating a rapid return on investment. These results affirm that oyster farming operations managed by Tomita Suisan Co., Ltd. are economically viable and offer promising potential for sustainable development and expansion in similar marine environments.